Tests of a two-color interferometer and polarimeter for ITER density measurements. (25th October 2017) - Van Zeeland, M A; Carlstrom, T N; Finkenthal, D K; Boivin, R L; Colio, A; Du, D; Gattuso, A; Glass, F; Muscatello, C M; O'Neill, R; Smiley, M; Vasquez, J; et al.
Abstract: A full-scale 120 m path length ITER toroidal interferometer and polarimeter (TIP) prototype, including an active feedback alignment system, has been constructed and undergone initial testing at General Atomics. In the TIP prototype, two-color interferometry is carried out at 10.59 μ m and 5.22 μ m using a CO2 and quantum cascade laser (QCL) respectively while a separate polarimetry measurement of the plasma induced Faraday effect is made at 10.59 μ m. The polarimeter system uses co-linear right and left-hand circularly polarized beams upshifted by 40 and 44 MHz acousto-optic cells respectively, to generate the necessary beat signal for heterodyne phase detection, while interferometry measurements are carried out at both 40 MHz and 44 MHz for the CO2 laser and 40 MHz for the QCL. The high-resolution phase information is obtained using an all-digital FPGA based phase demodulation scheme and precision clock source. The TIP prototype is equipped with a piezo tip/tilt stage active feedback alignment system responsible for minimizing noise in the measurement and keeping the TIP diagnostic aligned indefinitely on its 120 m beam path including as the ITER vessel is brought from ambient to operating temperatures. The prototype beam path incorporates translation stages to simulate ITER motion through a bake cycle as well as other sources of motion or misalignment. Even in the presence of significant motion, the TIP prototype is able to meet ITER's density measurement requirements over 1000 s shot durations with demonstrated phase resolution of 0.06° and 1.5° for the polarimeter and vibration compensated interferometer respectively. TIP vibration compensated interferometer measurements of a plasma have also been made in a pulsed radio frequency device and show a line-integrated density resolution of δ nL = 3.5 × 10 17 m −2 .